Efficiency in the banking industry of Central and Eastern Europe - Tran, Le Dung (2009)
This paper investigates the bank efficiency of 10 Central and Eastern Europe over the period 2006-2008. Applying Data Envelopment Analysis to a sample data of 155 commercial banks, it is found that the level of bank efficiency in CEE increased over the study period. The result is robust after testing by Tobit regression. The results indicate that bank efficiency is positively related to capital ratio but negatively associated with nonperforming loans. However, there is no clear evidence for the relationship between bank size and bank efficiency. Moreover, the level of bank efficiency in Baltic countries is higher than that in Non-Baltic countries but the difference is not significant.